SISTEM PAKAR DIAGNOSA PENYAKIT ALERGI PADA ANAK BERBASIS WEB DENGAN METODE FORWARD CHAINING DI KOTA BATAM - luthan, nanda (STKIP PGRI Sumatera Barat, 2017)
The need for information systems is a very important requirement for running business processes. As the development of technology is very necessary when an information technology really supports the information systems required form. Kano method can be used to determine the need for patient information systems. With the process of the Kano method used is based on the need for information systems. because the method aims to mengatagorikan canoe will need attribute information systems. ignorance of the service attributes can cause a negative for the company services. It therefore requires an information system that can meet the needs of patient information so users of patient information is needed to support the company's performance